More haste, less speed? Relationship between response time and response accuracy in gamified online quizzes in an undergraduate engineering course - Liang, Zilu (Frontiers in Education, 2024)
This study delves into the relationship between students' response time and response accuracy in Kahoot! quiz games, within the context of an app development course for first year university students. Previous research on response time in standardized tests has suggested that longer response time are often linked to correct answers, a phenomenon known as speed-accuracy trade-off. However, our study represents one of the initial investigations into this relationship within gamified online quizzes. Unlike standardized tests, each of our Kahoot! quiz modules consisted of only five single choice or true/false questions, with a time limit for each question and instantaneous feedback provided during game play. Drawing from data collected from 21 quiz modules spanning from 2022 to 2023, we compiled a dataset comprising 4640 response-time/accuracy entries.Mann-Whitney U tests revealed significant differences in normalized response time between correct answers and wrong answers in 17 out of the 21 quiz modules, with wrong answers exhibiting longer response time. The effect size of this phenomenon varied from modest to moderate. Additionally, we observed significant negative correlations between normalized overall response time and overall accuracy across all quiz modules, with only two exceptions. These findings challenge the notion of the speed-accuracy trade-off but align with some previous studies that have identified heterogeneity speed-accuracy relationships in standardized tests. We contextualized our findings within the framework of dual processing theory and underscored their implications to learning assessment in online quiz environments.